O real como poliedro: a mímesis em Zero e A festa - Oliveira, Júlia de Mello Silva (2019)
Since Zero (1975, Ignácio de Loyola Brandão) and A festa (1976, Ivan Ângelo) were published, the criticism about these works, in general, has analyzed them as experimental novels, justifying this experimental feature due to the context from which they have emerged, the Brazilian military dictatorship. It means, in short, that criticism focus on their fragmentary aspect and their multiplicity of point of views enclosed by them as a direct consequence (of the chaos) of conjuncture that they portray. However, aiming to illuminate another point of this discussion about the relationship between these novels and real that they evoke, through the review of the criticism’s monophony, this research, considering authoritarian regime as an intensifier of their aesthetic work, takes for hypothesis that such novels’ form are legatee of Representational Crisis from the end of nineteenth century. Thus, if we consider Brandão (2005), Bakhtin (2010) and Luiz Costa Lima (2009) theories together, we take into account that the novel is a protean genre (constituted by the contact with other textual and discursive genres) which centralizes mimesis and, hence, fiction issues. Thereby, because its metamorphic character, novel was transformed through time, until 19th century, inside a Western thinking paradigm – which has been consolidated, with variations – essentially metaphysic or substantialist that goes into crises at the turn of the 20th century, transforming the understanding of the relationship between Subject-Reality-Truth. This update, based on Pellegrini (2007;2009) and Lima (2003;2014), in literary terms, culminated on “representational crises” and “mimesis reconsideration”, causing a recomprehention of literary categories, especially narrative, as a consequence of the new conception of the Subject seen as a fractured catalytic prism of a real that turns polyhedral, subjetctly constructed from the way each individual (through his/her history) apprehends it, of which time is disruptive and space heterogeneous or disorded. Materially, it accrues from that refracted aesthetic, a set of aesthetic-representational techniques in accordance with the idea of plurality of faces and versions of the real and proportional to the diversity of ways of apprehending it. Therefore, Zero and A festa are novels with a form (without a center and with an absent center, respectively) intensified by the dictatorial conjuncture, but of an earlier origin, which goes back to the changes brought to literature, to the narrative in particular, by the critical-problematic consciousness about the relativity of concepts as real, truth, subject and representation.